PENERAPAN MODEL PEMBELAJARAN SAVI MATA PELAJARAN IPAS MATERI PERUBAHAN WUJUD ZAT PADA MURID KELAS IV SDN PAKIS V SURABAYA - Fajar Sodik; Hery Setiyawan; Suprihatien (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was initiated due to low student participation in IPAS learning, the dominance of teacher-centered instruction, and sub-optimal student understanding of changes in the states of matter. The purpose of this study was to describe the teacher's classroom management, student learning activities, cognitive learning outcomes, and student responses after implementing the SAVI (Somatic, Auditory, Visual, Intellectual) learning model on the topic of changes in the states of matter in the fourth grade of SDN Pakis V Surabaya. This research employed a descriptive quantitative approach with a One-Shot Case Study design involving 25 fourth-grade students as subjects. Data were collected through observations of the teacher's classroom management, observations of student learning activities, learning achievement tests, and student response questionnaires, which were then analyzed descriptively. The results showed that the teacher's classroom management achieved a mean score of 4.87 (Very Good), and student learning activities obtained a mean score ranging from 3.68 to 4.74 (Very Good). The cognitive learning outcomes indicated a classical learning mastery of 88% with a class average of 79.6, successfully meeting the predetermined mastery criteria. Furthermore, student responses to the implementation of the SAVI learning model reached 100% (Very Positive). Based on these findings, it can be concluded that the SAVI learning model is effectively implemented to improve classroom management quality, student activities, learning outcomes, and foster positive responses in IPAS learning at the elementary school level.